Kualitas Hidup Pada Lanjut Usia Yang Mengalami Sakit Osteoartritis Di Desa Gumpang Kecamatan Kartasura - Oktarina, Intan; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Quality of life was finished research since 20 years in people with chronic disorder, the one of was osteoarthritis, it was a degenerative disease and primary cause of painful. Painful increase when carry out activities, function disorder and body structur e makes someone activities become limits. Osteoarthritis was the part of arthritis, as such as degenerative disease. Caused was much factors and signed indicate change hypertrofic in the stricken bone area, and lost of cartilago progresivelly. The aims of this study was to identify quality of life elderly with osteoarthritis in Gumpang village, Kartasura. This study was used descriptive desain and used cross -sectional or made in one time, at May 2016. As many 70 elderly participate in this study, 20 of th em was man and 50 is woman. The results was showed quality of life elderly in Gumpang village with indicator WHOQOL - BREF instrumens composed of quality and physical health generally, psycology, social relationships and environments, from the calculated result was best part of responden are in a poor category . Painful and incompetent at activities was become primary problem had been around of patient with osteoarthritis.